CORPORATE E-MAIL SERVICE GOOGLE APPS AS AN INSTRUMENT OF ACTIVITY OF ORGANIZATIONAL-EDUCATIONAL UNITS OF THE HIGHER EDUCATIONAL INSTITUTION - Кarpenko А.С. (Journal of Information Technologies in Education (ITE), 2017)
The advantages of usage of cloud technologies, particularly, of Gmail service Google Apps in work of organizational-educational units of higher educational institutions are analyzed in this work. The main accents are put concerning usage of corporate e-mail Gmail service Google Apps, with the help of which informational-analytical support of activity of organizational-educational units of the University is provided. The author of the publication underlines key advantages of Gmail and analyses its opportunities. Main characteristics of corporate e-mail Gmail service Google Apps are described. It is identified that implementation of corporate e-mail Gmail service Google Apps is a part of creation of certain information system, that will ensure united information space of a modern higher educational institution. Effective organization of educational process, that was used by methodist of organizationaleducational units (Scientific-methodological centre of research, scientific projects and programs of Borys Grinchenko Kyiv University) in the work of corporate mail Gmail service Google Aps is analyzed and presented. It is identified, that creation and improvement of mechanisms of building corporate content with the help of Gmail service Google Apps will allow the collaborators of organizational-educational units of the higher educational institution to plan and organize educational process. Such organization of educational process optimizes the activity of organizational-educational units of higher educational institutions.